2019
DOI: 10.3343/alm.2019.39.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation Between the RealStarPneumocystis jiroveciiPCR Kit and the AmpliSensPneumocystis jirovecii(carinii)-FRT PCR Kit for DetectingP. jiroveciiin Non-HIV Immunocompromised Patients

Abstract: Background Real-time PCR is more sensitive than microscopic examination for detecting Pneumocystis jirovecii . We compared the performance of two assays for detecting P. jirovecii DNA: the RealStar Pneumocystis jirovecii PCR Kit 1.0 CE (Altona Diagnostics, Hamburg, Germany) and the AmpliSens Pneumocystis jirovecii ( carinii )-FRT PCR kit (InterLabService Ltd., Mosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The percentage of positive results was more variable for the "possible PCP" category, ranging from 54.5% (Bio-Evolution) to 86.4% (AmpliSens PCR), but all four assays were effective for PCP diagnosis. More recently, the performance of the RealStar P. jirovecii PCR Kit 1.0 EC (Altona Diagnostics, Hamburg, Germany) was compared with the AmpliSens PCR assay (Huh et al, 2019). The positive and negative percent agreements were 100 and 96.6%, respectively, and kappa was 0.92.…”
Section: Pneumocystis Jirovecii Pcrmentioning
confidence: 99%
“…The percentage of positive results was more variable for the "possible PCP" category, ranging from 54.5% (Bio-Evolution) to 86.4% (AmpliSens PCR), but all four assays were effective for PCP diagnosis. More recently, the performance of the RealStar P. jirovecii PCR Kit 1.0 EC (Altona Diagnostics, Hamburg, Germany) was compared with the AmpliSens PCR assay (Huh et al, 2019). The positive and negative percent agreements were 100 and 96.6%, respectively, and kappa was 0.92.…”
Section: Pneumocystis Jirovecii Pcrmentioning
confidence: 99%
“…in the literature. [8][9][10][11][12][13][14] Most of these kits target the mtLSU gene and show good performance for PCP diagnosis. A Working group of the International Society for Human and Animal Mycology recently evaluated 19 PCR assays, including 9 commercial kits, 6 and found that most commercial kits display a specificity of 100% and a sensitivity between 88.8 and 100% for P jirovecii DNA detection.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, in the only other study that evaluated the RealStar ® Pneumocystis jirovecii PCR Kit for PCP diagnosis, the positivity rate was 100% for BAL specimens, but only 20% for sputum/endotracheal aspirates. 13 This is probably due by the procedure for obtaining these respiratory specimens.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to PJ qPCR assays, the choice of target genes for amplification remains an open issue [7]. Recently, Huh et al [19] showed the similarity of two commercial assaysone of which was capable of amplifying the mitochondrial large subunit (mtLSU) of a ribosomal RNA gene-in detecting low PJ loads in BAL fluids. Very recently, Dellière et al [20] found that an automated commercial reverse-transcriptase qPCR (~2.2 h workflow) was more sensitive than their in-house qPCR assays (~5 h workflow), which amplified both mtSSU and mtLSU for detecting PJ in respiratory samples.…”
Section: Discussionmentioning
confidence: 99%